“Cupuaçu” (Theobroma grandiflorum): A brief review on chemical and technological potential of this Amazonian fruit - Jaqueline de Araújo Bezerra; Renilto Frota Corrêa; Edgar Aparecido Sanches; Carlos Victor Lamarão; Paulo César Stringheta; Evandro Martins; Pedro Henrique Campelo (Food Chemistry Advances)
Theobroma grandiflorum (Willd. Ex Spreng.) K. Schum. (“cupuaçu” ou cupuassu) belongs to the Malvaceae family whose pulp has a characteristic acidic flavor and a strong aroma allowing its consumption of juices, ice cream, creams, yogurt, and jelly. In addition, vegetable oil can be extracted from its seeds to produce a type of chocolate known as ``cupulate''. T. grandiflorum fruit contains organic acids, phenolic and volatile compounds, among which, some are related to antioxidants, anti-glycemic, and anti-inflammatory properties. Due to all these characteristics mentioned, the Amazonian “Cupuaçu” has great potential for technological applications mainly in food technology, with products and processes based on its extracts rich in bioactive compounds, pulp, or seeds.